Novation and indemnity as ways to terminate an obligation - V. V. Rasskazova (Bulletin of Kharkiv National University of Internal Affairs)
In modern contractual practice, novation and the transfer of the indemnity are quite relevant ways of terminating the obligation, which makes it necessary to deepen the characteristics of the distinguishing features and the principles of distinguishing the mentioned mechanisms for terminating the civil obligation.